Environmental Sustainability and Business Models in the Spanish Publishing Industry - Magadán Díaz, Marta; Rivas García, Jesús Israel (Springer, 2022)
The general objective of this work is to know the motivations that drive a publisher to be environmentally sustainable. The specific goals are the following: (a) to identify one or those environmentally sustainable business models from a Life Cycle Analysis perspective, and (b) to propose strategies to improve environmental sustainability in publishing organizations. The method used to carry out this research is the focus group: 20 Spanish publishers selected via convenience sampling and divided into two focus subgroups. From the analysis of the interviews, the main proposals are the following: an optimal selection of eco-efficient materials, the use of packaging with less environmental impact, reusable, or recyclable, combined with energy-efficient modes of transport, using more sustainable vehicles or green and move towards a print-on-demand model. Finally, this research concludes that the Spanish publishing industry has a wide margin of action to incorporate numerous improvements in terms of environmental sustainability.
Keywords: business models; environmental sustainability; publishing industry; Spain; Scopus; Emerging